Scenario-Based Framework for National Energy Storage Integration in Decarbonization Pathways - Hassan, Marwa; Yazawa, Nobuo; Richao Cong (International Journal of Sustainable Energy Planning and Management, 2025)
The integration of large-scale energy storage is pivotal for enabling re- liable, affordable, and decarbonized national power systems. This study introduces a scenario-based strategic planning framework to guide the de- ployment of storage under varying policy and technological futures. Four national-scale scenarios are examined to explore how different planning approaches affect emissions, cost, and grid stability. The results show that strategic early investment in storage—as modeled in Scenario A—can lead to a 50% storage penetration rate by 2050, avoid 220 million metric tons of carbon dioxide emissions, and reduce the Levelized Cost of Energy from 112 to 76 USD per megawatt-hour. Scenario A also demonstrates the most cost-effective reliability enhancement, achieving a cost per avoided blackout hour of 105,263 USD. In contrast, Scenario D, which assumes policy inaction, results in only 20 gigawatts of installed storage capacity by 2050, an 18% reduction in renewable energy curtailment, and a per- sistently high Levelized Cost of Energy of 118 USD per megawatt-hour. These findings underscore the critical role of storage in supporting na- tional decarbonization and highlight the need for coordinated planning. The proposed framework serves as a practical decision-support tool for aligning storage investments with long-term energy and climate goals.